2014
DOI: 10.1371/journal.pone.0091843
|View full text |Cite
|
Sign up to set email alerts
|

“Being Flexible and Creative”: A Qualitative Study on Maternity Care Assistants' Experiences with Non-Western Immigrant Women

Abstract: BackgroundSeveral studies conducted in developed countries have explored postnatal care professionals' experiences with non-western women. These studies reported different cultural practices, lack of knowledge of the maternity care system, communication difficulties, and the important role of the baby's grandmother as care-giver in the postnatal period. However, not much attention has been paid in existing literature to postnatal care professionals' approaches to these issues. Our main objective was to gain in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 14 publications
11
29
0
Order By: Relevance
“…It has been noted that refugees seek to meet basic needs, such as safety, nutrition, sheltering, and health care, and are unable to experience aspects of a ‘quality life’ instead of leading a qualified life, because they often come from low socioeconomic backgrounds (Turkish Ministry of Interior General Directorate of Immigration, 2016). The women in this study described how they were unable to prepare for childbirth due to financial problems and other factors related to poverty, which is consistent with a study conducted on immigrants in the Netherlands (Boerleider et al, ). The women in this study also identified that they had heavy domestic duties, and this impacted their ability to access health care during pregnancy and the postnatal period, as well as their general health and well‐being.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…It has been noted that refugees seek to meet basic needs, such as safety, nutrition, sheltering, and health care, and are unable to experience aspects of a ‘quality life’ instead of leading a qualified life, because they often come from low socioeconomic backgrounds (Turkish Ministry of Interior General Directorate of Immigration, 2016). The women in this study described how they were unable to prepare for childbirth due to financial problems and other factors related to poverty, which is consistent with a study conducted on immigrants in the Netherlands (Boerleider et al, ). The women in this study also identified that they had heavy domestic duties, and this impacted their ability to access health care during pregnancy and the postnatal period, as well as their general health and well‐being.…”
Section: Discussionsupporting
confidence: 89%
“…Refugee women have to cope with motherhood, protecting family integrity, and financial troubles (Murray, Windsor, Parker, & Tewfik, 2010;Hoban & Liamputtong, 2013 , 2016). The women in this study described how they were unable to prepare for childbirth due to financial problems and other factors related to poverty, which is consistent with a study conducted on immigrants in the Netherlands (Boerleider et al, 2014). The women in this study also identified that they had heavy domestic duties, and this impacted their ability to access health care during pregnancy and the postnatal period, as well as their general health and well-being.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The participants found it challenging to provide effective counselling to women whose participation in physical activity was limited by cultural expectations. Similar results have been reported in studies exploring maternity care assistants and midwives providing postpartum care [ 23 , 24 ]. These studies, performed in a Dutch setting, describe how the work with immigrant women needs to be flexible and creative, especially addressing issues related to lack of financial resources, low socioeconomic status, and family pressure.…”
Section: Discussionsupporting
confidence: 88%